MUSIC FESTIVALS AS AN IMPORTANT DIRECTION OF CULTURAL COOPERATION BETWEEN UZBEKISTAN AND UNESCO (ON THE EXAMPLE OF “SHARQ TARONALARI”) - U.A.Sattorov (International Journal of Literature and Language Studies, 2026)
This article examines the active cooperation between Uzbekistan and UNESCO in promoting and preserving the history, culture, and arts of Uzbekistan at the international level. The study pays particular attention to the profound reforms implemented in the cultural sphere following the country's independence, the strengthening of the legal framework governing the sector, and the revival of national values and traditions. It also provides detailed information on international conferences and arts festivals organized in the country’s historic cities, with a special focus on the “Sharq Taronalari” (Melodies of the East) International Music Festival, currently recognized as the largest music festival in the Central Asian region. The research explores the history of the festival, its organizational processes and objectives, as well as its contemporary role in promoting the culture and arts of the Uzbek people worldwide. The study is based on relevant legal and regulatory documents, scholarly research, academic literature, and materials from periodical publications related to the subject.